Assessing the Impact of Nutritional Status on Psychomotor Development in Infants Aged 0-23 Months in the Gahombo Health District, Burundi - Baseka, Michel; Niyukuri, Jonathan; Ndayishimiye, Alice; Az-Eddine, Sedki; Ntakarutimana, Vestine (International Journal of Child Health and Nutrition, 2025)
This study aims to assess the influence of malnutrition on the psychomotor development of children aged 0–23 months in the Gahombo health district. The survey was conducted from 12 to 27 July 2024. The results show disharmonious psychomotor development in children suffering from severe acute malnutrition (SAM) and moderate acute malnutrition (MAM) when compared to their adequately nourished peers. The ability to hold the head without support, sit, crawl, walk independently, pronounce simple words, babble, and track familiar faces is significantly affected in malnourished children. Only 9.7% of MAM and 2.7% of SAM children walked independently at 12 months of age, in contrast to 39.2% of adequately nourished children. Furthermore, the ability to pronounce "papa" and "maman" or to babble and follow a familiar face was much lower in malnourished children (p < 0.05). These delays were more pronounced in cases of severe malnutrition. Therefore, malnutrition has a profound influence on psychomotor development in children under two years of age. The study highlights the importance of early intervention and appropriate nutritional care in mitigating the impact of these disorders.